Kolaborasi Stakeholders dalam Meningkatkan Kualitas Manajemen Sekolah - Hilwah Azzahro; Idea Facile Putri; Nur Aisyah Retno Wulan; Hesti Kusumaningrum (PT PUSTAKA CENDEKIA GROUP, 2025)
In every education system, there is certainly an expectation for the success of the development of educational institutions. The responsibility for the education of a nation is not solely the task of the central government, but also the responsibility of local governments and every stakeholder involved. As key educational management elements, stakeholders have diverse roles and responsibilities. Stakeholders in improving the quality of school management consist of teachers, parents, school principals, school committees, and the government. All these aspects must then be considered, and an effective collaboration model and strategies must be chosen to improve school management's quality. The goal is to have a positive impact on the improvement of school management quality and to be able to face collaboration challenges as well as to find solutions to those challenges.